INTEGRASI MUSIK DAN DEEP TALK: INOVASI PEMBELAJARAN KOMUNIKASI INTERPERSONAL DI KALANGAN MAHASISWA - Rosalina, Indah Fajar (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2025)
This study aims to introduce an innovative approach to teaching interpersonal communication for first-year university students through the integration of music and deep talk. At the early stage of their academic journey, students often face challenges in developing interpersonal communication skills due to limited experience and a tendency to feel more comfortable interacting in digital spaces. To address this issue, the study designed a paired conversation activity to directly implement interpersonal communication practice. Students were paired and asked to choose from categories of questions related to life, love, as well as future aspirations and hopes. Each pair was given 30 minutes to engage in dialogue on the assigned topic, accompanied by the background music “Dunia Tipu-tipu” by Yura Yunita. They were then asked to analyze their partners’ responses based on DeVito’s principles of interpersonal communication: empathy, supportiveness, openness, positivity, and equality. Data were collected through students’ reflective notes and lecturers’ observations. The findings reveal that music successfully created a warmer conversational atmosphere, facilitated openness, and strengthened the empathetic dimension of communication. Furthermore, students reported an increased sense of closeness with new peers and greater awareness of the importance of active listening. This study concludes that integrating music and deep talk is an effective and innovative learning strategy for fostering interpersonal communication among first-year students. ABSTRAK Penelitian ini bertujuan memperkenalkan inovasi pembelajaran komunikasi interpersonal bagi mahasiswa semester awal melalui integrasi musik dan deep talk. Mahasiswa pada tahap awal perkuliahan umumnya menghadapi tantangan dalam membangun komunikasi interpersonal karena keterbatasan pengalaman dan kecenderungan lebih nyaman berinteraksi di ruang digital. Untuk itu, penelitian ini merancang aktivitas percakapan berpasangan mahasiswa untuk mengimplementasi komunikasi interpersonal secara langsung. Mahasiswa dibagi berpasangan, kemudian memilih kategori pertanyaan terkait kehidupan, cinta, serta masa depan dan harapan. Setiap pasangan diberi waktu 30 menit untuk berdialog dengan topik yang sudah ditetapkan dan didukung latar musik lagu “Dunia Tipu-tipu” karya Yura Yunita. Mereka kemudian diminta menganalisis lawan bicara berdasarkan prinsip komunikasi interpersonal menurut DeVito, yakni empati, supportiveness, openness, positivity, dan equality. Data dikumpulkan melalui catatan refleksi mahasiswa dan observasi dosen. Hasilnya menunjukkan bahwa musik mampu menciptakan suasana percakapan yang lebih hangat, memfasilitasi keterbukaan, serta memperkuat dimensi empati dalam komunikasi. Selain itu, mahasiswa melaporkan meningkatnya rasa kedekatan dengan teman baru dan kesadaran akan pentingnya mendengarkan aktif. Penelitian ini menyimpulkan bahwa integrasi musik dan deep talk merupakan strategi pembelajaran inovatif yang efektif untuk membangun komunikasi interpersonal di kalangan mahasiswa semester pertama.